Performance of Sesamum (Sesamum indicum L.) Grown with Production Components under New Alluvial Zone of West Bengal - Mondal, Koushik; Gunri, Sunil Kumar; Goswami, Saumi; Das, Soumyajyoti; Paul, Anusree; Jana, Kalyan; Banerjee, Sibaji (International Journal of Bio-resource and Stress Management, 2025)
Experiment was carried out in the Jaguli Instructional Farm, Jaguli, Bidhan Chandra Krishi Viswavidyalaya, Nadia, West Bengal, India during the summer seasons (1st week of February to 3rd week of May) of 2020 and 2021 to study the performance of sesame with major production components for its economic yield. The experiment was laid down in a randomized block design with 3 replications, comprising of 12 combination of different resource management viz., T1- F.P. (Fertilizer+Irrigation+Weeding+Plant protection), T2- F.P. – Fertilizer, T3- F.P. -Irrigation, T4- F.P. – Weeding, T5- F.P. – Plant protection, T6- F.P. – (Fertilizer+Irrigation), T7- F.P. – (Fertilizer+Weeding), T8- F.P. – (Fertilizer+Plant protection), T9- F.P. – (Weeding+Irrigation), T10- F.P. – (Plant protection+Irrigation), T11- F.P. – (Weeding+Plant protection), T12- F.P. – (Fertilizer+Irrigation+Weeding+Plant protection). Among the four production components (fertilizer+irrigation+weeding+plant protection) the most crucial component was fertilizer component followed by weeding, irrigation and plant protection associated with seed yield. Ignoring the fertilizer component resulted in a 25.6% decrease in seed output; this was followed by reductions of 23.9% in weeding, 14.3% in watering, and 3.7% in plant protection. The yield drop was noted more strongly when two components were omitted, and it was learnt in proportionally greater amounts when the fertilizer component was omitted together with the weeding. When all components were sacrificed the seed yield was reduced severely (83.7%). The higher BCR was found under the treatment [FP-(Weeding+PP)]. Hence, in order to maximize profit, the fertiliser component of sesame was an even more important resource component that could not be sacrificed.